Polypyrrole Composite - A Potential Material for the Removal of Acid Dyes - Palanisamy, P.N.; Agalya, A.; Sivakumar, P. (Asian Journal of Chemistry, 2013)
The present research work provides information on the dye removal potential of polypyrrole saw dust composite, prepared by reinforcement of natural wood saw dust (obtained from Euphorbia tirucalli L wood) and polypyrrole matrix phase. Dye adsorption on polypyrrole composite was characterized in terms of adsorption isotherm, kinetics and the parameters studied were initial dye concentration, contact time, pH and temperature. The kinetic data obtained at different initial dye concentration and temperatures were studied using pseudo-first order and pseudo-second order model. The equilibrium data were analyzed by Freundlich and Langmuir isotherm model. The equilibrium isotherm data were fitted well with Langmuir isotherm model. The maximum monolayer adsorption capacities calculated by Langmuir model were 243.9, 243.90, 250 and 256.41 mg/g for acid orange10 at 30, 35, 40 and 45 ºC respectively. The thermodynamic parameters including DGº, DHº and DSº were evaluated and suggesting the feasible, spontaneous, endothermic nature of ion exchange adsorption with weak vader Walls force of attraction. Activation energy for the adsorption of acid orange10 by polypyrrole composite was 2.0704 kJ/mol. Isosteric heat of adsorption calculated using Clasius-Clapeyron equation also supported the ion exchange adsorption process in which forces of attraction between dye molecules and polypyrrole composite is weak.